Targeting multiple cannabinoid anti‐tumour pathways with a resorcinol derivative leads to inhibition of advanced stages of breast cancer. (5th September 2014) - Murase, Ryuichi; Kawamura, Rumi; Singer, Eric; Pakdel, Arash; Sarma, Pranamee; Judkins, Jonathon; Elwakeel, Eiman; Dayal, Sonali; Martinez‐Martinez, Esther; Amere, Mukkanti; Gujjar, Ramesh; Mahadevan, Anu; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose The psychoactive cannabinoid Δ9‐tetrahydrocannabinol (THC) and the non‐psychoactive cannabinoid cannabidiol (CBD) can both reduce cancer progression, each through distinct anti‐tumour pathways. Our goal was to discover a compound that could efficiently target both cannabinoid anti‐tumour pathways. Experimental Approach To measure breast cancer cell proliferation/viability and invasion, MTT and Boyden chamber assays were used. Modulation of reactive oxygen species (ROS) and apoptosis was measured using dichlorodihydrofluorescein and annexin/propidium iodide, respectively, in combination with cell flow cytometry. Changes in protein levels were evaluated using Western analysis. Orthotopic and i.v. mouse models of breast cancer metastasis were used to test the activity of cannabinoids in vivo. Key Results CBD reduced breast cancer metastasis in advanced stages of the disease as the direct result of down‐regulating the transcriptional regulator Id1. However, this was associated with moderate increases in survival. We therefore screened for analogues that could co‐target cannabinoid anti‐tumour pathways (CBD‐ and THC‐associated) and discovered the compound O‐1663. This analogue inhibited Id1, produced a marked stimulation of ROS, up‐regulated autophagy and induced apoptosis. Of all the compounds tested, it was the most potent at inhibiting breast cancer cell proliferation and invasion in culture and metastasis in vivo. Conclusions and Implications O‐1663 prolonged survival in advanced stages of breast cancer metastasis. Developing compounds that can simultaneously target multiple cannabinoid anti‐tumour pathways efficiently may provide a novel approach for the treatment of patients with metastatic breast cancer.